2009
DOI: 10.1111/j.1651-2227.2009.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Early nasal intermittent positive pressure ventilation versus continuous positive airway pressure for respiratory distress syndrome

Abstract: Among preterm infants with suspected RDS, early use of NIPPV reduces the need for intubation and mechanical ventilation compared to CPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 15 publications
2
87
2
4
Order By: Relevance
“…9 During the study period, whether in the nIPPV or nCPAP method, the occurrence of side effects was not observed, similar to that noted by other authors. 1,6,7,11,19 Barrington et al and Davis et al were unanimous in affirming that nIPPV is a useful and effective method to increase the benefits of nCPAP in the prevention of extubation failure of premature infants in the first hours after extubation. 1, 8 Likewise, Khalaf et al consider nIPPV as more effective than nCPAP in the weaning of premature infants with respiratory distress syndrome (RDS) using mechanical ventilation, and recommend that nIPPV should be used as the primary extubation method even in premature infants with impaired pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 During the study period, whether in the nIPPV or nCPAP method, the occurrence of side effects was not observed, similar to that noted by other authors. 1,6,7,11,19 Barrington et al and Davis et al were unanimous in affirming that nIPPV is a useful and effective method to increase the benefits of nCPAP in the prevention of extubation failure of premature infants in the first hours after extubation. 1, 8 Likewise, Khalaf et al consider nIPPV as more effective than nCPAP in the weaning of premature infants with respiratory distress syndrome (RDS) using mechanical ventilation, and recommend that nIPPV should be used as the primary extubation method even in premature infants with impaired pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…Kishore et al believe that with nIPPV there is better alveolar recruitment, with improved residual functional capacity. 11 Moretti et al consider that nIPPV may increase upper airway patency by creating high pressure in the pharynx and promoting intermittent inflation of the pharynx, thereby activating the respiratory rhythm. 22 In their study, the authors performed pulmonary function tests and found that during nIPPV the pulmonary volumes (tidal volume and minute volume) were significantly higher compared to nCPAP, and the values of the transcutaneous PaCO 2 were also significantly lower compared to those in the nCPAP group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study that used our SNIPPV guidelines 19 for NIPPV has also reported benefit. 20 A detailed description of the equipment and technique in providing (S)NIPPV, as practiced by our group, has been included in the Appendix.…”
Section: Techniquementioning
confidence: 99%
“…12 Primary mode SNIPPV (after early intubation and surfactant administration), in a RCT, had a significantly improved primary outcome of BPD/death, compared to the group that continued on ETT IPPV, with no difference in other common neonatal morbidities. 18 In a RCT using primary mode NIPPV (using NIPPV as first line of therapy), the infants randomized to the NIPPV group were more likely to stay extubated 13,14 and had less BPD. 13 In another RCT, primary mode NIPPV (after early intubation and surfactant administration) resulted in more successful extubation and less BPD.…”
mentioning
confidence: 99%